Exploring positive welfare measures: preliminary findings from a prototype protocol in loose housing dairy cattle farms - Mattiello, Silvana; Celozzi, Stefania; Soli, Federica Manila; Battini, Monica (Frontiers in Veterinary Science, 2024)
Following the increasing interest about the development of indicators of positive welfare and affective state in farm animals, the aim of this research is to present some preliminary results on the application of a prototype protocol based exclusively on positive welfare measures in 20 loose housing dairy cattle farms (6 on deep litter with straw, 14 in cubicles). The protocol included only indicators of positive welfare and emotional states: feeding and resting synchronization, rumination during resting, comfortable lying postures, no visible eye white, relaxed ear postures, percentage of cow contacts with humans in the Avoidance Distance test. Potential benefits in terms of housing, feeding and management were then related to these variables (Mann-Whitney U test). Qualitative Behavior Assessment (QBA) was also carried out and analyzed by Principal Component Analysis to explore the effect of factors that were not evenly distributed in our sample (number of feed distributions, access to pasture, presence of paddock or environmental enrichments, automatic milking systems). When hay was included in the diet, higher feeding synchronization (93.7±1.6 vs 52.2±4.7%; p<0.01), percentage of cows with relaxed ear postures (35.8±5.4 vs 15.5±2.1%; p<0.01) and percentage of cows with no visible eye white (55.9±17.0 vs 36.6±4.1%; n.s.) were recorded. A higher level of feeding synchronization was observed also when the feeding places/cow ratio was >1 (72.1±9.9 vs 53.8±5.8%), although differences were not significant (p=0.14). Deep litter had a more positive effect than cubicles on comfort at resting, with a significantly higher percentage of ruminating cows (65.8±10.2 vs 34.2±3.7%; p<0.01), a higher percentage of cows with no visible eye white (55.6±9.9 vs 33.1±3.7%; p<0.05) and a higher percentage of cows in a more comfortable posture, with stretched legs (14.3±5.1 vs 5.6±1.6%; p=0.09). QBA highlighted the most positive emotional state in the only farm that allowed access to pasture. This study represents a first attempt to apply a protocol for on-farm welfare evaluation based exclusively on the use of positive welfare indicators and provides suggestions on possible benefits (e.g., deep litter, feeding places/cow ratio >1, hay in the diet and access to pasture) to enhance dairy cattle welfare.